Variation in the Oxytocin Receptor Gene Is Associated with Face Recognition and its Neural Correlates - Westberg, Lars; Henningsson, Susanne; Zettergren, Anna; Svärd, Joakim; Hovey, Daniel; Lin, Tian; Ebner, Natalie C.; Fischer, Håkan (Frontiers in Behavioral Neuroscience, 2016)
The ability to recognize faces is crucial for daily social interactions. Recent studies suggest that intranasal oxytocin administration improves social recognition in humans. Oxytocin signaling in the amygdala plays an essential role for social recognition in mice, and oxytocin administration has been shown to influence amygdala activity in humans. It is therefore possible that the effects of oxytocin on human social recognition depend on mechanisms that take place in the amygdala – a central region for memory processing also in humans. Variation in the gene encoding the oxytocin receptor (OXTR) has been associated with several aspects of social behavior. The present study examined the potential associations between nine OXTR polymorphisms, distributed across the gene, and the ability to recognize faces, as well as face-elicited amygdala activity measured by functional magnetic resonance imaging during incidental encoding of faces. The OXTR 3’ polymorphism rs7632287, previously related to social bonding behavior and autism risk, was associated with participants’ ability to recognize faces. Carriers of the GA genotype, associated with enhanced memory, displayed higher amygdala activity during face encoding compared to carriers of the GG genotype. In line with work in rodents, these findings suggest that, in humans, naturally occurring endogenous modulation of OXTR function affects social recognition through an amygdala-dependent mechanism. These findings contribute to the understanding of how oxytocin regulates human social behaviors.